Requirement Of N, P, K, And S For Yield Maximization Of Bitter Gourd (Momordica charantia) - Nasreen, Shamima; Ahmed, R; Uddin, M Nazim (Bangladesh Journal of Agricultural Research, 2013)
Experiments were carried out at the research field of Horticulture Research Centre, BARI, Joydebpur during kharif seasons of 2010 and 2011 to find out the requirement of N, P, K, and S application for obtaining higher yield of bitter gourd (var. BARI Karola-1). There were 14 treatment combinations comprising four levels each of N (0, 90, 20,150 kg/ha), P (0, 20, 40, 60 kg/ha), K (0, 40, 80, 120 kg/ha), and S (0, 20, 30, 40 kg/ha). A blanket dose of 2 kg B, 4 kg Zn, and 5 ton cowdung/ha was used. The maximum fruits/plant, fruit size, and single fruit weight and yield of bitter gourd was achieved from the treatment N120 P40 K80 S30 kg/ha and the lowest from the control treatment. The yield benefit for the best treatment over the control was 208% in 2010 and 137% in 2011. Response to N and P was more pronounced in comparison to K and S. The yield increased linearly with increasing rates of N up to 120 kg/ha, P up to 40 kg/ha, K up to 80 kg/ha, and S up to 30 kg/ha and thereafter decreased. The highest gross margin (Tk. 486867/ha) and marginal rate of return (8083%) was also obtained from the same treatment. Overall results reveal that application of N120 P40 K80 S30 kg/ha along with a blanket dose of 2 kg B, 4 kg Zn and 5 ton cowdung/ha appears to be the best treatment for maximizing the yield of bitter gourd in Grey Terrace Soil (AEZ-28) of Joydebpur. Bangladesh J. Agril. Res. 38(2): 355-361, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15896